On New Sandwich Results of Univalent Functions Defined by a Linear Operator - Mihsin, Bassim Kareem; Atshan, Waggas Galib; Alhily, Shatha S. (Iraqi Journal of Science, 2022)
In this research paper, we explain the use of  the convexity and the starlikness properties of  a given function  to generate  special properties of differential subordination and superordination functions in the classes of analytic functions that have  the form   in the unit disk. We also show the significant of  these properties to derive sandwich results when the Srivastava- Attiya operator   is used.